Multidecadal Variations in the Relationship between the NAO and Winter Precipitation in the Hindu Kush-Karakoram - Filippi, Luca; Palazzi, Elisa; von Hardenberg, Jost; Provenzale, Antonello (Journal of Climate, 2014)
Winter precipitation over the Hindu Kush-Karakoram (HKK) range in the western Himalayas is generated by westerly perturbations whose dynamics is affected by the North Atlantic Oscillation (NAG). Larger precipitation is typically recorded during the positive NAO phase. In this work, the relationship between the NAO and winter precipitation in the HKK is explored further, using an ensemble of precipitation datasets and the 40-yr ECMWF Re-Analysis (ERA-40) and Twentieth Century Reanalysis (20CR) data. The mechanisms underlying this relationship are discussed, with a focus on the secular variations that occurred in the last century. The NAO exerts its control on HKK precipitation by altering the intensity of westerly winds in the region of the Middle East jet stream (MEJS). Results indicate that evaporation from the Persian Gulf, the northern Arabian Sea, and the Red Sea plays an important role. During positive NAO phases, westerlies are strengthened and enhanced evaporation occurs from these basins owing to higher surface wind speed. The extra moisture combines with stronger westerlies and results in enhanced moisture transport toward the HKK. Precipitation datasets covering the twentieth century show an alternation of periods of strong and weaker influence of the NAO on precipitation in the HKK. It is found that these variations are associated with changes in the spatial pattern of the NAO: the relative position of the two centers of action of the NAO determines to what extent it can modulate the MEJS, affecting precipitation in the HKK.